2012
DOI: 10.5897/jhmt12.019
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of service quality of Nigerian airline using servqual model.

Abstract: The study tries to evaluate the service quality of a Nigerian Airline with objectives to determining what constitutes the service variables in the Nigerian air transport Industry, how satisfied are the passengers with the services of the above mentioned airline and suggest to managers of these airlines on how to improve and promote satisfaction level of passengers. Data was collected from the respondent using a well structured questionnaire to discover the perception of the passengers of the airline under stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…More so, there is a scarcity of academic studies on travellers" satisfaction on the quality of service experienced and perception of basic airport attributes contributing to the quality of service experienced by travellers. Known studies about air transportation in Nigeria examined travellers" decision making on airlines, the service quality offered by a Nigerian airline, the determinants of domestic airline patronage in Nigeria, and customers" perception of service quality in domestic airlines services (Adiele & Etuk, 2017;Chikwendu, Ejem, & Ezenwa, 2012;Ukpere, Stephens, Ikeogu, Ibe, & Akpan, 2012). These studies focused on the airline, not the airport or issues regarding the availability and adequacy of airport elements that contribute to travellers" experience.…”
Section: Statement Problemmentioning
confidence: 99%
“…More so, there is a scarcity of academic studies on travellers" satisfaction on the quality of service experienced and perception of basic airport attributes contributing to the quality of service experienced by travellers. Known studies about air transportation in Nigeria examined travellers" decision making on airlines, the service quality offered by a Nigerian airline, the determinants of domestic airline patronage in Nigeria, and customers" perception of service quality in domestic airlines services (Adiele & Etuk, 2017;Chikwendu, Ejem, & Ezenwa, 2012;Ukpere, Stephens, Ikeogu, Ibe, & Akpan, 2012). These studies focused on the airline, not the airport or issues regarding the availability and adequacy of airport elements that contribute to travellers" experience.…”
Section: Statement Problemmentioning
confidence: 99%
“…According to Etuk, Anyadighibe, James & Mbaka (2021), for servicedelivery companies like the airline industry, in today's era of consumer enlightenment and sophistication to be able to succeed, they must have the capability to consistently deliver highquality services that meet or surpass customers' anticipations. The air transport industry in Nigeria has shown strong growth of 11.4 percent which has been sustained since 2007 (Chikwendu, Ejem & Ezenwa, 2012). In like manner, the airline industry in Nigeria has also seen a massive growth in recent times with an average growth rate of over 8 percent and has also witnessed passenger increased from 293,613 to 543379 in 2012 alone (Chikwendu, et al, 2012).…”
Section: Introductionmentioning
confidence: 97%
“…The air transport industry in Nigeria has shown strong growth of 11.4 percent which has been sustained since 2007 (Chikwendu, Ejem & Ezenwa, 2012). In like manner, the airline industry in Nigeria has also seen a massive growth in recent times with an average growth rate of over 8 percent and has also witnessed passenger increased from 293,613 to 543379 in 2012 alone (Chikwendu, et al, 2012). According to Etuk & Akpan (2015), the airlines foundation is built on proven safe, reliable and on-time air transportation while delivering to customers the highest standard of professionalism and efficient customer services.…”
Section: Introductionmentioning
confidence: 99%
“…The authors observed that the academic research about the products and services offered by the airline companies was mostly conducted with SERVQUAL-based surveys (Aydın & Yıldırım, 2012;Başfırıncı & Mitra, 2015;Chou et al, 2011;Du et al, 2012;Farooq et al, 2018;Ganiyu, 2017;Hapsari et al, 2016;Huang, 2009;Hussain et al, 2015;Hussain, 2016;Jiang & Zhang, 2016;Kağnıcıoğlu & Özdemir, 2016;Leong et al, 2015;Pakdil & Aydın, 2007). As another observation, travel review and rating sites focus mostly on accommodation businesses (Banerjee & Chua, 2016;Bayram, 2017;Cezar & Öğüt, 2016;Doğan, 2017;Hu & Chen, 2016;Min et al, 2014;Neirotti et al, 2016;Pacheco, 2016;Raguseo et al, 2017;Sparks et al, 2016) and food and beverage businesses (Bertan, 2016;Cheng & Ho, 2015;Dalgıç et al, 2016;Doğan et al, 2016;Erdem & Yay, 2017;Eren & Çelik, 2017;Kim et al, 2016;Taştan & Kızılcık, 2017;Zhu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%